Supporting service integration through early childhood education: challenges and opportunities in regional contexts - Neilsen-Hewett, Cathrine; de Rosnay, Marc; Singleton, Janine; Stouse-Lee, Kim (Frontiers in Education, 2023)
Children and families residing in regional Australia experience higher rates of vulnerabilities coupled with inadequate access to the early childhood health and early intervention services which pose increased risk to their health, development and wellbeing. The current study was designed to respond to the inherent complexity of supporting effective integrated service provision in regional communities, with a view to develop a model of effective service integration that leverages the capacity and opportunity of universal early childhood education (ECE) provision.The study adopted a qualitative multiple case study design to explore the perceptions of ECE professionals across six regional ECE services and two early intervention professionals operating from a regional early childhood intervention (ECI) organisation. Data included an initial audit of the service system landscape coupled with facilitated discussions (focus groups and interviews) to identify facilitators and challenges to service integration and current patterns of service usage and engagement.Results: Findings highlighted the foundational importance of relationships for establishing trust, engagement and service sustainability, as well as the need for embedding structural supports, including the professionalisation of educators, the utilisation of a key worker model, and staff retention. Systemic constraints, including limitations and inconsistencies in community infrastructure, program atrophy, and the complexity of referral systems, were seen to undermine effective service integration. Discussion: Findings speak to the potentiality of the ECE context as a hub for effective service integration within a functional practice framework for ECE. We conclude by offering a suggested model to ensure service connections, and enhance professional capacity and sustainability.